LEARNING IMPLEMENTATION USING CHATGPT MEDIA AT SMA NEGERI 1 SUKABUMI - Tantan Hadian; Asep Ikhwan Awaluddin; Deti Rostini; Ade Tutty R Rosa (JURNAL PAJAR (Pendidikan dan Pengajaran), 2023)
This paper describes the use of ChatGPT in learning. The research is a qualitative descriptive study with a case study at SMA Negeri 1 Sukabumi in West Java Province Indonesia. The research begins with a survey, which involves the distribution of questionnaires to 13 learning subject teachers in grade 10 and 69 tenth-grade students who were selected randomly. The questionnaire results were analyzed as a basis for further research, including in-depth interviews, observations, and document studies. Classroom observations were carried out on two teachers who have implemented learning using ChatGPT. To deepen the results of the observations, interviews were distributed to the two teachers and three students who were randomly selected from the observed classes. The research findings indicate that learning using ChatGPT can assist teachers in preparing and directing students in the teaching and learning process. With teacher guidance, students are expected to gain knowledge more comprehensively and deeply by asking specific questions that align with learning objectives. The teacher’s competence to guide students in the use of ChatGPT in terms of n achieving learning objectives determines the achievement of learning outcomes from each student. ChatGPT, as one of the Artificial Intelligence (AI) technologies, offers new challenges in the field of education. The research in this paper provides insights into how this AI technology can be utilized in classroom learning